PARENTING CHILDREN IN EQUAL EDUCATION PACKAGE B IN FATHER'S ORPHANAGE, SEBANGAU DISTRICT, PALANGKA RAYA CITY, CENTRAL KALIMANTAN - Kusnida Indrajaya; Hendrowanto Nibel; Susan Daniel; Arnalda Anastasia Siburian; Amri R Girsang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Parenting is a process that aims to improve and support the physical, emotional, social and intellectual development of a child from infancy to maturity. Parenting comes from the word pattern and care. In the Big Indonesian Dictionary, pattern means system, way of working. While foster means guide, lead. So that it can be interpreted as a way of guiding or leading children. This research was conducted using a quantitative approach to the survey method. Qualitative research is research where the researcher is placed as a key instrument, the data collection technique is carried out by combining and the data analysis is inductive. This research was conducted in four stages, namely: 1) research preparation stage, 2) research implementation stage, 3) data analysis stage, and 4) conclusion drawing stage. The subjects of this study were caretakers of the Ayah Bunda Orphanage and Children from the Ayah Bunda Orphanage in Sebangau District, Palangka Raya City, Central Kalimantan. The instrument used in this study was interviews given to research subjects.